Pro JavaScript Techniques - Resig, John (Apress : Imprint: Apress, 2007)
Pro JavaScript Techniques is the ultimate JavaScript book for the modern web developer. It provides everything you need to know about modern JavaScript, and shows what JavaScript can do for your web sites. This book doesn't waste any time looking at things you already know, like basic syntax and structures. Expert web developer and author John Resig concentrates on fundamental, vital topics-what modern JavaScripting is (and isnt), the current state of browser support, and pitfalls to be wary of. The book is organized into four sections: Modern JavaScript development using JavaScript the object-oriented way, creating reusable code, plus testing and debugging DOM scripting updating content and styles, plus events, and effect and event libraries How Ajax works, overcoming problems, and using libraries to speed up development of Ajax applications The future of JavaScript looking at cutting edge topics like JSON, HTML5, and more All concepts are backed up by real-world examples and case studies, and John provides numerous reusable functions and classes to save you time in your development. There are also up-to-date reference appendixes for the DOM, events, browser support (including IE7), and frameworks, so you can look up specific details quickly and easily.